EMPIRICAL DIMENSION OF PHILOSOPHICAL GEOGRAPHY - Tavadze, Giorgi (European Scientific Journal, ESJ, 2014)
Geography explores relationships between society and the natural environment. Humans transform the natural environment, which in its turn influences and, to a certain degree, conditions society. Some geographical elements (for example place and space) exert a powerful influence on individual and collective identities, self-awareness and actions. Philosophical geography should study relations between these geographical elements and individual and collective identities and human agency. The empirical dimension of philosophical geography is the most interesting, but perhaps also the least investigated part of this discipline. In order to elucidate how the conceptual framework of philosophical geography can help the empirical research, the present article discusses the expedition which was organised by the Institute of Philosophy and Social Sciences under the auspices of Grigol Robakidze University (Tbilisi, Georgia) in Upper Khevsureti in the summer of 2012.